Investigação da viabilidade da redução do consumo de energia elétrica em edificações residenciais através da aplicação de soluções de conforto ambiental passivo - Pires, Josiane Reschke (Universidade do Vale do Rio dos Sinos, 2013)
The concern with sustainability brought the need for optimization of the energy resources to reduce the consumption of electric energy and of natural resources. One of the aspects is the need to adapt the buildings to the climate in which they are located, reducing the energy consumption of housing. The aim of this research is to investigate the technical and economic viability of applying some criteria of thermal performance in residential buildings. The methodology is based on the identification of the costs and energy in the life cycle of projects based on environmental comfort on passive (natural) and active (artificial) ways, detailing the influence on energy consumption of the building. It was applied in residential projects, both vertical and horizontal, of lower and middle class, in two distinct microclimates (Porto Alegre and Bento Gonçalves, southern Brazilian cities), examining alternatives of envelope, insulation and the use of architectural façade elements. To analyze the thermal performance was adopted the Brazilian standard NBR 15575 and degree-hour method, with BIM modeling through Revit/Autodesk and for the thermal simulation Ecotect/Autodesk and EnergyPlus. The life cycle of the proposed case studies was analyzed by considering a period of 50 years, comparing the costs and embodied energy of alternatives. As a second measure of sustainability, energy efficiency was also analyzed with the Brazilian standard of energy efficiency Procel Edifica. The results showed that with the increment of envelope’s insulation there are improvement of thermal comfort, of 54%, and energetic economy, in both climates, with a payback period of 2 to 6 years, in some cases.
Investigation of the viability of reducing energy consumption in residential buildings through the implementation of passive strategies for environmental comfort
Keywords: Desempenho térmico; Análise do ciclo de vida; Energia incorporada; Selo procel; EnergyPlus; Thermal performance; Life cycle analysis; Embodied energy; Procel standard; ACCNPQ::Engenharias::Engenharia Civil